Intimate partner violence against women living with HIV in Lesotho: evidence from the 2023/24 DHS data set - Gebresilassie Tadesse; Girum Nakie; Gidey Rtbey; Techilo Tinsae; Setegn Fentahun; Mulualem Kelebie; Tigist Kifle Tsegaw; Getachew Muluye Gedef; Getasew Kibralew; Fantahun Andualem (BMC Public Health)
Abstract Background Intimate partner violence (IPV) is a widespread violation of women’s rights and a critical public health issue, especially in sub-Saharan Africa. Women living with HIV (WLHIV) are particularly vulnerable due to gender power imbalances, HIV-related stigma, and the bidirectional relationship between violence and HIV acquisition. In Lesotho, where HIV prevalence is among the highest globally, limited evidence exists on IPV against WLHIV. This study aims to estimate the prevalence and factors associated with IPV against women living with HIV in Lesotho. Methods Data were drawn from the 2023/24 Lesotho DHS. A weighted sample of 467 women aged 15–49 years who were living with HIV was included. IPV was defined as having experienced at least one form of emotional, physical, or sexual violence by a partner/husband. Multivariable logistic regression was conducted to identify factors associated with IPV. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were reported. Results Based on the findings of the study, 34.19% (95% CI: 30.01–38.63) of WLHIV experienced at least one form of IPV in the last 12-month preceding the survey. Moreover, the 12-month prevalence for physical, emotional, and sexual violence respectively was 25.48%, 19.61%, and 10.07%. In the final model analysis, having multiple sexual partners and sexually transmitted infections (STIs) other than HIV in the past 12-month, not having own asset, disclosing HIV status, living with a jealous partner/husband and a male-headed household, and region of residence were significantly associated with experiencing IPV. Conclusion More than one-third of reproductive-age WLHIV in Lesotho experience IPV in the last 12-month preceding the survey, with key associated factors. Integrated interventions that combine HIV care with IPV screening, education, economic empowerment, and behavioral change communication are essential to mitigate IPV among WLHIV in Lesotho by considering these factors.